PENINGKATAN KEMAMPUAN GENERIK MAHASISWA BIOLOGI FKIP UR PADA MATAKULIAH GENETIKA DAN EVOLUSI MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) - Darmawati ' ' (Biogenesis, 2015)
This research was conducted with the aim to improve the generic skill biology FKIP UR students through the application of PBL model. The subject of research is 4th semester biology students year 2011/2012 that include 50 peoples. The type of this research is research action class. Instrument’s reseach is a learning device (Syllabus, SAP, LKM, textbook) and data collecting tool (LKM and assessment sheets). Technique of data analysis is in a descriptive. The result showed that the average of generic skill students to compeleted the LKM for first (I) cycle is 71.10% (good) increased to 75.60% (good) for second (II) cycle. The average of generic skill students made a map of thought for the first (I) cycle that 74.73% (good) increased to 81.56% (excellent) for second (II) cycle. So, thapplication of PBL model can improve the generic skill biology FKIP UR students on the subject of genetics and evolution.Keywords : Genetics and Evolution, Generic Skill, Problem Based Learning (PBL)